ON SOME FEATURES OF THE FORMATION OF THE KARAKALPAK STORY OF THE 30S - EARLY 50S OF THE ХХ CENTURY - Amanova Aysultan Abdirazakovna (American Journals, 2023)
This article discusses the problem of the development of the Karakalpak story of the 30s - early 50s of the twentieth century, the formation of literature focused on new European artistic principles in their specific Soviet version.
Keywords: The Karakalpak story, determinism, motivated narration, normativism, themes, plot, narration, figurative and speech means.